Comparison between single‐site and multiport robot‐assisted hysterectomy in obese patients with endometrial cancer: An Italian multi‐institutional study. Issue 2 (29th December 2019) - Corrado, Giacomo; Mereu, Liliana; Bogliolo, Stefano; Cela, Vito; Gardella, Barbara; Sperduti, Isabella; Certelli, Camilla; Pellegrini, Alice; Posar, Giulia; Zampa, Ashanti; Tateo, Saverio; Gadducci, Angiolo; et al.
Abstract: Background: The aim of this study is to compare robotic single‐site hysterectomy (RSSH) and robotic multiport hysterectomy (RMPH) for endometrial cancer (EC) in obese patients in terms of surgical outcomes. Methods: This retrospective study compares RSSH with RMPH in obese patients with EC and FIGO stages I to II divided in three classes according to their body mass index (BMI): class A (30‐34.9 kg/m 2 ), class B (35‐39.9 kg/m 2 ), and class C (>40 kg/m 2 ). Results: We included 225 patients (RSSH: 76; RMPH: 149). The operative time and estimated blood loss (EBL) were lower in the A class of the RSSH group. The EBL and the conversion rate increased when the BMI increased in the RSSH group. The hospital stay was higher in the A class of the RMPH group. Conclusions: The advantages of RSSH in terms of reduced invasiveness remain true only in the first BMI class, whereas they are lost when the BMI increased.